Interoperability between health information systems in the hospital context - Fernandes, João Gabriel (2021)
The information systems had a positive effect on the health service by reducing the physical documentation, more available information to monitor the patient and safer data storage. On the other hand, there was a negative impact due to an increase of diverse systems operating which demanded more training and support to hospitals structure aligned with the lack of interoperability standards that promote the patient´s data sharing between them. Therefore, this dissertation focused on analysing the existent interoperability between information systems in the Portuguese health service, determine the key aspects to establish communication among them, and the consequences it has on the healthcare professional´s routines. Interviews were conducted with healthcare professionals and hospital suppliers to collect their experience on interacting with this technology, their opinion about the influence it has on the hospital´s routine, and the potential measures to improve the current situation. This research concluded that the lack of interoperability and an unfriendly interface generates a complex use of the systems with a high number of clicks and slower navigation to execute the tasks that can cause loss of time for healthcare professionals. Besides, the public hospital demonstrated to have a higher number of IS suppliers and lower levels of integration between systems compared with private hospitals. Lastly, it was demonstrated that an organisational culture oriented to the technology change and a strategic plan to adapt to the hospital's approach is necessary to a successful implementation of health information systems.